Optic neuropathy endemic in secondary school children in Dar es Salaam, Tanzania. Issue 2 (9th August 2009) - Bowman, R J C; Wedner, S; Bowman, R F; Masanja, H; Bunce, C; Wood, M L; Gilbert, C
Abstract : Aim: To investigate the prevalence and causes of optic neuropathy, reported as epidemic in 1997, among secondary school students in Dar es Salaam, Tanzania. Patients and methods: First year students (n = 10 892) from 63 secondary schools located within 30 km from the base hospital were interviewed and had a visual acuity (VA) screening test. Students failing the 6/12-line in either eye were defined as having "poor eyesight" and referred to the base hospital where an optometrist re-tested VA and refracted them. An ophthalmologist examined students with VA of 6/12 or worse in either eye and visual impairment was defined as VA of worse than 6/12 with best correction. Associations between optic neuropathy, socioeconomic status and educational results were investigated. Results: Students' ages ranged from 12 to 22 (mean 15.2) years; 50.6% were male. The prevalence of optic neuropathy was 0.3 (SD 0.051)%. The condition affected older students and was associated with the family having fewer economic possessions (car, computer, television). Optic neuropathy accounted for 19/33 (58%) of bilateral visual impairment cases. No effect of the disease on educational performance was identified. Conclusion: Optic neuropathy remains a significant problem in this population and can now be termed endemic rather than epidemic. Further research into its causes is required.